Legionnaires’ disease outbreak in Victoria - No authors listed (Communicable Diseases Intelligence, 2000)
The Victorian Department of Human Services has confirmed that as of 3 May 2000, the number of cases of Legionnaires' disease from an outbreak associated with the Melbourne Aquarium, has reached 58.